Pengembangan Kapasitas Petani Melalui Program Pendidikan Vokasional untuk Diversifikasi Usaha Agribisnis di Desa Yosodadi - Suci Amalia; Edi Sulaiman; Ade Rahmad Kurniawan; Irfan Azhari; Lilik Febrianti (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2022)
Abstract This community service activity aims to increase the capacity of farmers in Yosodadi Village through a vocational education program designed to support agribusiness diversification. The main problem faced by the assisted community is their dependence on monoculture farming and the lack of technical and entrepreneurial skills to develop alternative agribusiness opportunities. Using the Community-Based Research (CBR) approach, the program involved farmers in all stages of the process, from problem identification to implementation and evaluation. A series of participatory activities were conducted, including horticulture training, agricultural product processing workshops, entrepreneurship sessions, and the establishment of a demonstration plot. The results show that 10 new agribusiness units were formed, farmer awareness of record-keeping and business planning increased, and local leadership began to emerge among younger farmers. This program not only improved technical skills but also encouraged social transformation through the strengthening of group institutions and the development of a collaborative culture. The findings confirm that integrating vocational education with community empowerment can effectively address structural challenges in rural agriculture. Keywords: Farmer Capacity